Human rights oversight of correctional institutions in Australia - Naylor, Bronwyn (European journal of criminology, 2021)
Australia has recently ratified the Optional Protocol to the Convention against Torture (OPCAT) in order to improve the oversight of Australia’s prisons and detention centres, following major human rights violations exposed in them in 2016. Ratification offers an opportunity to appraise the effectiveness of monitoring and oversight in Australia, and the limitations of human rights protections in the Australian context. Australia’s prisons and youth detention centres are to be monitored by a network of independent inspecting bodies, which are likely to include existing Ombudsman and human rights bodies. The Office of the Commonwealth Ombudsman has the task of coordinating the new inspection bodies. This article reviews the existing protections of rights in Australia and considers the implications of ratification of OPCAT. The article concludes that implementation will require consideration of the effectiveness of the current bodies monitoring prisons and youth detention and their capacity to take on the role of preventing human rights violations, including their independence from government, as the states and territories decide on the establishment of their National Preventive Mechanisms. Implementation will also require an understanding of Australia’s historical ambivalence towards international human rights engagement and the impact of its federated system.